2022
DOI: 10.1007/s12079-022-00686-y
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive network map of IL-17A signaling pathway

Abstract: Interleukin-17A (IL-17A) is one of the member of IL-17 family consisting of other five members (IL-17B to IL-17F). The Gamma delta (γδ) T cells and T helper 17 (Th17) cells are the major producers of IL-17A. Aberrant signaling by IL-17A has been implicated in the pathogenesis of several autoimmune diseases including idiopathic pulmonary fibrosis, acute lung injury, chronic airway diseases, and cancer. Activation of the IL-17A/IL-17 receptor A (IL-17RA) system regulates phosphoinositide 3-kinase/AKT serine/thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Aberrant signaling of IL-17 implicates the pathogenesis of several autoimmune diseases, including idiopathic pulmonary fibrosis, acute lung injury, chronic airway disease, and cancer 58 . Literature research on the enrichment gene of the IL-17 signaling pathway in the first place showed that CCL12 chemokine produced by macrophages and epithelial cells is a fibrogenic medium, and CCL12 could promote the development of fibrosis [59][60][61] . Pena-Philippides et al 62 reported that CCL12 and CXCL5 cytokine expression affect the secretion of IL-17.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant signaling of IL-17 implicates the pathogenesis of several autoimmune diseases, including idiopathic pulmonary fibrosis, acute lung injury, chronic airway disease, and cancer 58 . Literature research on the enrichment gene of the IL-17 signaling pathway in the first place showed that CCL12 chemokine produced by macrophages and epithelial cells is a fibrogenic medium, and CCL12 could promote the development of fibrosis [59][60][61] . Pena-Philippides et al 62 reported that CCL12 and CXCL5 cytokine expression affect the secretion of IL-17.…”
Section: Discussionmentioning
confidence: 99%
“…After 1 year, all three groups had an improvement in psoriasis severity which was significant (anti-TNF-α; 8.9 (6.0-14.7) to 2.7 Next, we tested whether changes in serum BD2 were concomitant with a reduction of psoriasis severity (Table 2). We found that patients undergoing anti-TNFα biologic treatment over 1 year exhibited a 51% reduction in serum BD2 (27,499.3 ng/mL, p = 0.0062) and those treated with anti-IL17A, a 45.8% reduction (72,866.9-39,503 ng/mL, p = 0.0046). However, a significant reduction (12.9%) in serum BD2 was not observed in patients lacking biological therapy (87,281.1-76,068.66 ng/mL, p = 0.127), though psoriasis disease severity was diminished (p = 0.0249).…”
Section: Bd2 Levels Are Reduced In Psoriasis Subjects Undergoing Anti...mentioning
confidence: 81%
“…Altered bursts of IL-6 in COPD have been reported, which may make the system more susceptible to SARS-CoV-2 in-burst. Upregulated concentrations of Th2/M2 cytokines, including IL-6, CCL22, IL-4, IL-13, and IL-10, were observed in the bronchoalveolar lavage of COPD individuals, with IL-13 being particularly elevated [ 26 , 27 ].…”
Section: Pathophysiology With Sars-cov-2 Ace-2 An Open Chapter?mentioning
confidence: 99%